Blood serum thyroid hormone levels and rumen protozoa in merino rams at different environmental temperatures - Ercan Keskin; Tufan Keçeci (Eurasian Journal of Veterinary Sciences)
In the study, a total ol 18 merino rams which were at the same age, similar body weight and healthy were used, The levels of thyroid hormone were measured in blood serum, ruminal pH and protozoa count were determined and the species of protozoon were identified in rumen contents at different environmental temperatures in the different seasons. The levels of blood serum total thyroxin and total triiodothyronine, ruminal pH and protozoa count were found to be lower amounls in the animals at 23.7JC and 20.0 % relative humidity (RH). when compared to the same values ol the rams at 3.2"C and 63.3 % RH. The percentages o( the protozoon species did not significantly alter depended on the environmental temperatures in the experiment.